The Comparison of Macular Thickness in Diabetic Patients without Proliferative Diabetic Retinopathy using Optical Coherence Tomography (OCT) at Prof. Dr. R D Kandou General Hospital, Manado, Indonesia - Ade John Nursalim (Journal of Global Pharma Technology, 2020)
Background: Macular thickening that occurs in diabetic retinopathy has been known as one of the primary causes of vision loss functions in patients with diabetic retinopathy. In order to prevent further complications due to macular thickening, Optical Coherence Tomography (OCT) has been used as a diagnostic tool in diabetic retinopathy. This study aims to evaluate the importance of OCT in promoting early detection in retinal thickening as diagnostic tools and proper exams to diminish the chance of visual acuity related to diabetic retinopathy. Method: A case-control observational study was conducted among 22 subjects with Diabetes Mellitus Type-2 (DM-2) from the medical record of the Ophthalmology-Vitreoretinal Division at Prof. dr. R.D. Kandou State General Hospital, Manado from March-December 2018 period. They were divided into 11 patients with mild and moderate non–proliferative diabetic retinopathy (NPDR) and 11 non-diabetic patients’ group. OCT was used to evaluate the macular thickness in both groups. Data were analyzed using SPSS version 20 for Windows. Result: Most of subjects were female (59.1%), age 45-50 years (31.8%), ≥ 10 years duration of DM-2 (63.6%), refractive errors of 0.00-(-3.00) and 0.00-(+3.00) (33.3%), and HbA1c levels ≥6.5 % (54.5%). There was a statistically significant difference of the central macular thickness between NPDR (257.32±76.94 µm) and non-NPDR patients (213.14±19.23 µm) (p=0.006) by using OCT. Conclusion: Optical Coherence Tomography (OCT) could be used to compare the significant differences of macular thickness between diabetic patients without proliferative diabetic retinopathy at Prof. Dr. R D Kandou General Hospital, Manado, Indonesia. Keywords: Macular Thickness, Diabetic Retinopathy, Optical Coherence Tomography.